Keabsahan Putusan Pengadilan yang Belum Inkracht sebagai Novum dalam Pengajuan Peninjauan Kembali - Salim, Hardy; Halim, Yoefanca; Tirayo, Adriel Michael (Jurnal Ilmiah Penegakan Hukum, 2019)
A judicial institution has criteria that must be met, namely principles that are open, corrective, and recordive. The broadest opportunity to submit corrections and recordings of decisions that have permanent legal force (inkracht) deemed unfair by justice seekers can be done through a Judicial Review. However, the Judicial Review is very limitative, one of them with the requirement for novum. But the regulation of conditions can be said to be a condition as a novum not strictly regulated. By looking at this matter, the research is carried out with the aim of finding out the validity of court decisions which have not been inkracht as novum in the submission for reconsideration. This study is using a normative research method. In conclusion, court decisions that have not been inkracht as novum in submitting judicial review are valid because they need to prioritize the value of justice and truth before legal certainty. As long as the prerequisites in Article 263 paragraph (1) of the Criminal Procedure Code have been fulfilled, and one of the requirements in paragraph (2) has been fulfilled.